Sliding wear behavior of magnetron sputtered chromium carbide thin films. Issue 4 (13th June 2016) - Beliardouh, Nasser Eddine; Nouveau, Corinne; Kaleli, Hakan
Abstract : Purpose: The purpose of this technical paper is to investigate the friction and wear behavior of inexpensive and durable cutting tools, developed for wood machining using duplex treatment. Design/methodology/approach: Cr–(WC–Co) coatings were deposited onto carburized low-alloy steel substrate by a reactive magnetron sputtering. The total coating thickness was approximately 2 μm. Unlubricated wear tests have been performed using a disc sample sliding against an alumina ball (Al2 O3 ) and a wood (beech) pin. Findings: The paper provides information about the effect of duplex treatment on the surface properties of low-alloy steel against wood and offers practical help for the researchers in coating topic. Originality/value: Experimental results showed that sliding wear properties of the selected coatings are strongly dependent on the counter-face material. When tested against alumina balls, the wear mechanisms are oxidative wear followed by a combination of adhesive and abrasive wear, while a combination of an oxidative and adhesive wear was the main wear mechanism observed against a wood pin.